The Impact of Shared Values on CSR Programs in the Field of Vocational Education - Meldawita Meldawita; Dita Oki Berliyanti (International Journal Labs, 2023)
CSR programs in the field of sustainable education are very important in supporting sustainable development goals, namely the achievement of quality education. Industry involvement is an important factor in the realization of quality education, especially for vocational high schools, so that the competencies possessed by students and teachers are in accordance with the competencies needed by industry and the times. Therefore, it is interesting to explore more deeply what CSR programs are carried out by the industry to improve the quality of schools through increasing the competence of students and teachers and the impact felt by schools with this CSR program. The method used is a mixed method with concurrent embedded design ? where in this study qualitative method is the primary method used, while the quantitative method is used only to find supporting data. PT. X & PT. Y is two automotive companies that have been fostering vocational schools in Indonesia for more than 3 years, through CSR programs in the field of vocational education. The short-term goal of the program is to improve the competence of students and teachers. And the long-term goal of this program is to contribute to sustainable development goal (SDG) number 4, namely quality education. The results showed that CSR carried out by the industry had a positive impact on schools and companies, and in its implementation using the concept of creating shared value (CSV).